MEMBANGUN KESADARAN LINGKUNGAN BERSIH DI SDN 1 PLOSOGENENG JOMBANG - Irianto, Bambang S.; Pratama, Alfian Diko; Ardiano, Aditya Rafli; Budhi W., M. Arief; Azhari, Riga Nurizqi (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Developing a clean-environment consciousness is a community outreach initiative carried out by the MBKM Internship Student Team, Faculty of Law, UPN "Veteran" East Java. The primary purpose of an environmental clean activity is to increase awareness of the clean environment at SDN Plosogeneng 1 Jombang in order to promote a clean and healthy environment. Clean, wholesome surroundings play a large role in creating a comfortable and productive learning environment. Clean environmental awareness activities involve SDN Plosgeneng 1 as a partner of these activities. By including 12 teachers as educators and 40 student SDN Plosgeneng 1, jointly displaying a clean and healthy environment in order to enhance the morale of learning activities in order to promote happy and happy teaching activities SDN Plosgeneng 1 Jombang. The habit of clean environmental awareness will always be the habit of all students in daily life not only in school circles but in all community environments.